2014
DOI: 10.1016/j.lfs.2014.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Using caffeine and other adenosine receptor antagonists and agonists as therapeutic tools against neurodegenerative diseases: A review

Abstract: Caffeine is the most consumed pychostimulant in the world, and it is known to affect basic and fundamental human processes such as sleep, arousal, cognition and learning and memory. It works as a nonselective blocker of adenosine receptors (A1, A2a, A2b and A3) and has been related to the regulation of heart rate, the contraction/relaxation of cardiac and smooth muscles, and the neural signaling in the central nervous system (CNS). Since the late 1990s, studies using adenosine receptor antagonists, such as Caf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 101 publications
(154 reference statements)
7
122
0
1
Order By: Relevance
“…These receptors are effectively inhibited by biologically relevant concentrations of caffeine at the micromolar range (Fredholm et al, 1999;Nehlig, 1999;Rivera-Oliver and Díaz-Ríos, 2014). Adenosine receptors are widely distributed in the brain, in which they are involved in various neural functions.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are effectively inhibited by biologically relevant concentrations of caffeine at the micromolar range (Fredholm et al, 1999;Nehlig, 1999;Rivera-Oliver and Díaz-Ríos, 2014). Adenosine receptors are widely distributed in the brain, in which they are involved in various neural functions.…”
Section: Discussionmentioning
confidence: 99%
“…16 A growing body of research shows that coffee drinkers may be less likely to develop type 2 diabetes, stroke, depression, and neurodegenerative diseases, including Parkinson's and Alzheimer's. [25][26][27] However, contradictory evidence in the literature about the effect of caffeine in the heart has been described. Thus, habitual moderate coffee intake has been associated with beneficial 28 or neutral 29 effects on cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects exerted by caffeine on cognitive functions have been documented [18], and it was reported that caffeine consumption prevents memory disturbances associated with ageing [19,20,21]. Also, increasing attention has been given to caffeine since its intake has been associated with a reduced neurological damage in several neurodegenerative diseases [22]. In fact, a decreased risk of developing Parkinson's disease (PD) [23,24] and Alzheimer's disease (AD) [25] was associated with a higher intake of coffee.…”
Section: Caffeine: Potential Beneficial Effectsmentioning
confidence: 99%